Contrasting population genetic patterns within the white-throated sparrow genome (Zonotrichia albicollis) - Maney Donna L; Huynh Lynn Y; Thomas James W (BMC Genetics, 2010)
Abstract Background The level of nucleotide diversity observed across the genome is positively correlated with the local rate of recombination. Avian karyotypes are typified by large variation in chromosome size and the rate of recombination in birds has been shown to be negatively correlated with chromosome size. It has thus been predicted that nucleotide diversity is negatively correlated with chromosome size in aves. However, there is limited empirical evidence to support this prediction. Results Here we sequenced 27 autosomal and 12 sex chromosome-linked loci in the white-throated sparrow (Zonotrichia albicollis) to quantify and compare patterns of recombination, linkage disequilibrium (LD), and genetic diversity across the genome of this North American songbird. Genetic diversity on the autosomes varied up to 8-fold, with the lowest diversity observed on the macrochromosomes and the highest diversity on the microchromosomes. Genetic diversity on the sex chromosomes was reduced compared to the autosomes, the most extreme difference being a ~300-fold difference between the W chromosome and the microchromosomes. LD and population structure associated with a common inversion polymorphism (ZAL2/2m) in this species were found to be atypical compared to other macrochromosomes, and nucleotide diversity within this inversion on the two chromosome arrangements was more similar to that observed on the Z chromosome. Conclusions A negative correlation between nucleotide diversity and autosome size was observed in the white-throated sparrow genome, as well as low levels of diversity on the sex chromosomes comparable to those reported in other birds. The population structure and extended LD associated with the ZAL2/2m chromosomal polymorphism are exceptional compared to the rest of the white-throated sparrow genome.